Antifungal 5,6-dihydrotetrazolo[1,5- c]quinazolines show promise against multidrug-resistant klebsiella pneumoniae - Antypenko, L.; Antypenko, O. M.; Lyashko, L.; Fominichenko, A.; Kozyrieva, V.; Антипенко, Олексій Миколайович (My University, 2025)
This study evaluated nineteen tetrazolo[1,5-c]quinazoline derivatives for antibacterial activity against a multidrug-resistant Klebsiella pneumoniae strain (resistant to 14 standard antibiotics) isolated from patient blood samples. Only two compounds demonstrated measurable activity in 0.125 – 64 mg/L range: compound 63 (carboxylic acid derivative) and compound 102 (2-chlorobenzyl acetamide), both achieving MIC values of 64 mg/L. These results contrast with previously reported potent antifungal activity (0.125 mg/L) of spiroderivatives, indicating organism-specific structural requirements. While the antibacterial activity is modest, this proof-of-concept study establishes 5,6-dihydrotetrazolo[1,5-c]quinazolines as potential scaffolds for developing novel antibacterial agents against resistant bacterial pathogens.